Immunometabolism and PI(3)K Signaling As a Link between IL-2, Foxp3 Expression, and Suppressor Function in Regulatory T Cells - Fan, Martin Y.; Turka, Laurence A. (Frontiers in Immunology, 2018)
CD4+ Foxp3+ regulatory T cells (Tregs) are an essential component of immune homeostasis. Modulation of Treg function has been proposed as a means of treating autoimmune conditions and preventing rejection of organ transplants, although achieving this goal will require a detailed understanding of Treg signaling pathways. Signaling within Tregs is known to differ considerably from that observed in other T cell subsets. Of note, Tregs are the only cell type known to constitutively express CD25, the main ligand-binding subunit of the IL-2 receptor. The PI(3)K/Akt/mTOR cascade constitutes a major signaling pathway downstream of IL-2 and is closely tied to cellular metabolism. Due to increasing recognition of the links between cellular fuel usage and immune cell function, the interplay between IL-2 signaling and Treg metabolism represents an important space for exploration and a potential approach for immunomodulation. Here, we discuss how IL-2 may affect Treg metabolism via PI(3)K signaling, as well as the effects of altered metabolism on Treg lineage stability and suppressor function.